ナンキョク オオガタ セツジョウシャ (SM100S) ノ カイハツ III. シャタイ ザイリョウ ノ ヨウセツ ブ テイオン ジンセイ - 作井, 新; サクイ, シン; 中島, 征志; ナカジマ, マサシ; Sakui, Shin; Nakajima, Masashi (1992)
P(論文) 南極氷床ドーム深層掘削計画用の南極大型雪上車(使用温度-50℃前後)の開発にあたって, 脆性破壊防止の観点より車体用鉄鋼材料の溶接部靭性について調査を行った。-50℃前後の低温環境下で稼働する車両の場合, シャルピー衝撃試験における破面遷移温度が-50℃であり, かつシャルピー衝撃値として20～29J/(cm)^2のセミキルド鋼, キルド鋼を用いれば脆性破壊を防止できることが経験的に知られている。そこでSS400,SL2N255,STPL380,STPL450の手溶接, (CO)_2溶接(供試鋼の板厚はいずれも約5mm, 溶接は単層溶接)継手部についてシャルピー衝撃試験を行った。その結果, 先の選定基準に従えば, 新雪上車の車体材料としてはSL2N255,STPL450が適当であることを確認した。 For the purpose of developing a new snow vehicle car (common use at temperature about -50℃) for the deep ice coring project at Dome Fuji, East Antarctica, the low temperature toughness of the welded joints of structural steel was investigated. It is empirically well known that in case of vehicles employed in a cold air temperature of about -50℃, the low temperature brittle fracture of the structural members does not take place, if one uses the semi-killed or the killed steel, for which 50% FATT'S (fracture appearance transition temperature) of the Charpy impact test is about -50℃ and Charpy impact values at -50℃ are 20–29J/(cm)^2. In the present paper, the Charpy impact test has been performed for both single pass SMAW and (CO)_2 arc welded joints of JIS steels of SS400,SL2N255,STPL380,and STPL450. The test results show that the JIS steels of SL2N255 and STPL450 can be used for the new vehicle, considering their toughness. departmental bulletin paper